Legal Analysis of Prosecution of Money Laundering Crimes (TPPU) Proceeds of Narcotics Crimes in Indonesian Criminal Law - Mayang Tari; Andri Winjaya Laksana (UNISSULA Semarang, 2025)
Abstract. Money laundering (TPPU) derived from narcotics crimes is an organized crime that has a broad impact on economic stability, security, and the effectiveness of law enforcement. Narcotics crimes often generate significant financial profits, leading perpetrators to employ various money laundering methods to disguise the origins of their proceeds. This study aims to analyze the legal aspects of prosecuting money laundering (TPPU) derived from narcotics crimes based on Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering and Law Number 35 of 2009 concerning Narcotics. The research method used is normative legal research with a statutory, conceptual, and case study approach. The results indicate that prosecutions of money laundering derived from narcotics crimes still face several obstacles, including the lack of evidence to prove the predicate crime, limited asset tracking, minimal coordination between law enforcement agencies, and increasingly complex asset disguising patterns. However, prosecutions can be conducted without having to wait for a final and binding court decision on the predicate crime, as long as there is sufficient preliminary evidence. Furthermore, implementing a